ANALISIS KANDUNGAN KALSIUM (Ca) PADA TANAMAN PORANG (Amorphophallus Oncophyllus) - Sahputra, Rachmat (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2025)
The nutritional content in porang plants, as with other plants, also contains carbohydrates, fats, proteins, minerals, vitamins and fiber. This study aims to obtain data on the average Calcium mineral content in Porang Plants. The analysis method uses an atomic absorption spectrometer (AAS) in flame emission mode. The sample solution containing Calcium is stored in a polyethylene bottle. Calcium has a maximum emission light at a wavelength of 422.7 nm, where the working procedure is that the sample is nebulized into a gas flame so that controlled excitation occurs with the Calcium resonance spectrum line at 422.7 nm isolated with an interference filter or with a light dispersing device with a prism or grating. The intensity of the emission light is measured with a photomultiplier, or photodiode. The light intensity at 422.7 nm will be approximately proportional to the Calcium concentration. The results of the analysis were obtained on 5 kg of wet porang plants, equivalent to 1 kg of dry porang tubers, which contained 112.3 g of calcium from dry flour, equivalent to 16.85 g of calcium from dry tubers, equivalent to 3.37 g of wet tubers.